Academic and Professional Career Outcomes of Medical School Graduates Who Failed USMLE Step 1 on the First Attempt - McDougle, Leon (Adv Health Sci Educ Theory Pract, 2012)
PURPOSE: This study sought to determine the academic and professional outcomes of medical school graduates who failed the United States Licensing Examination (USMLE) Step 1 on the first attempt. METHODS: This retrospective cohort study was based on pooled data from 2,003 graduates of six Midwestern medical schools in the classes of 1997 to 2002. Demographic, academic, and career characteristics of graduates who failed Step 1 on the first attempt were compared to graduates who initially passed. RESULTS: Fifty medical school graduates (2.5%) initially failed Step 1. Compared to graduates who initially passed Step 1, a higher proportion of graduates who initially failed Step 1 became primary care physicians (26/49 [53%] vs. 766/1,870 [40.9%]), were more likely at graduation to report intent to practice in underserved areas (28/50 [56%] vs. 419/1,939 [21.6%]), and more likely to take 5 or more years to graduate (11/50 [22.0%] vs. 79/1,953 [4.0%]). The relative risk of first attempt Step 1 failure for medical school graduates was 13.4 for African Americans, 7.4 for Latinos, 3.6 for matriculants > 22 years of age, 3.2 for women, and 2.3 for first generation college graduates. The relative risk of not being specialty board certified for those graduates who initially failed Step 1 was 2.2. CONCLUSION: Our observations regarding characteristics of graduates in our study cohort who initially failed Step 1 can inform efforts by medical schools to identify and assist students who are at particular risk of failing Step 1.